2023
DOI: 10.1186/s12903-023-02926-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of software updates on accuracy of intraoral scanners

Abstract: Background Digital workflow is showing an increasing tendency in everyday dentistry. Accuracy is essential during digital dental workflows for all indication areas. The present study aimed to evaluate the effect of software updates on the accuracy of intraoral scanner (IOS) devices. Methods 3Shape Trios 3 Pod with software versions 18.1.2. (TRI3_1) and 20.1.2. (TRI3_2); 3Shape Trios 4 Move, version 19.2.2. (TRI4_1); and 3Shape Trios 4 Pod, version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(35 reference statements)
0
12
1
Order By: Relevance
“…These variations in rankings may be attributed to differences in the chin model, materials, or implant brands evaluated in the studies. Furthermore, it has been demonstrated that software version differences in IOS, similar to model differences, can affect the accuracy and precision of digital scans [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…These variations in rankings may be attributed to differences in the chin model, materials, or implant brands evaluated in the studies. Furthermore, it has been demonstrated that software version differences in IOS, similar to model differences, can affect the accuracy and precision of digital scans [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Son et al 45 demonstrated a difference in the accuracy of the dental scanner used depending on the software program using 3D analysis. Schmalzl et al 46 reported that the accuracy of intraoral scanners was affected by software updates. Furthermore, Fortin et al 47 mentioned that differences in the software used could cause variations in the measurement results; they also compared the reliability difference between ImageJ and OsiriX.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the type of scanning technique used can significantly impact the repeatability and consistency of measurements. The superior repeatability of the plaster models could be attributed to the direct physical replication of the oral structures, minimizing potential errors associated with data processing and algorithmic calculations inherent in digital models [20,21]. During the intraoral scanning process, errors can be caused by factors such as surrounding soft tissue, the presence of saliva and bleeding, patients' movements, the size of the scanner head, limited mouth opening, and the experience of the operator [22].…”
Section: Discussionmentioning
confidence: 99%